Highly reliable spin-transfer torque magnetic RAM based physical unclonable function with multi-response-bits per cell - Zhang, Le (2015)
Memory-based Physical Unclonable Function (MemPUF) has gained tremendous popularity in the recent years to securely preserve secret information in computing systems. Most MemPUFs in the literature have unreliable bit generation and/or are incapable of generating more than one response-bit per cell. Hence, we propose a novel MemPUF exploiting the unique characteristics of Spin-Transfer Torque Magnetic RAM (STT-MRAM) that can overcome these issues. Bit generation in our STT-MRAM based MemPUF is stabilized using a novel automatic write-back technique. Also, the alterability of the Magnetic Tunneling Junction (MTJ) state is exploited to expand the response-bit capacity per cell. Our analysis demonstrated the advantage of our scheme in reliability enhancement (Bit-Error Rate from 10 −1 to 10 −6 in the worst-case under varying conditions) and response-bit capacity per cell improvement (from 1 bit to 1:48 bits). In comparison with the conventional MemPUFs, our approach is also better in terms of the average chip area and energy for producing a response-bit.